EMPOWERING COASTAL COMMUNITIES THROUGH THE ELEVATION OF BIENE HONEY PRODUCTS: STRENGTHENING BRANDING, PACKAGING, AND MARKET ACCESS - Mimin Sundari Nasution; Dadang Mashur; Zulkarnaini Zulkarnaini; Taryono Taryono; Harapan Tua; Masrul Ikhsan; Arya Arismaya Metananda (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to enhance the competitiveness of local products through the empowerment of coastal communities in Bengkalis Regency, particularly the Biene honey business group. The main problems faced by the partners are weak branding, simple packaging design, and limited market access, which hinder the honey products from competing broadly. The method used is Participatory Action Research (PAR) through training, mentoring, and joint evaluation stages. The interventions carried out include strengthening brand identity, redesigning packaging to meet food safety standards, and facilitating digital marketing through marketplaces and social media. The results of the program indicate an increase in partners’ capacity in business management, marketing, and product handling. The new Biene Honey brand identity has been registered as intellectual property, product packaging has become more attractive and hygienic, and market access has expanded through online sales channels and promotion via local media. Overall, this program has successfully fostered the economic independence of coastal communities by strengthening branding, packaging, and market access, while also contributing to the achievement of sustainable development goals, particularly in the areas of decent work, economic growth, and partnerships.